Aspectos Gerais Da Pandemia De COVID-19: Reflexões a Meio Caminho 2 2022
DOI: 10.22533/at.ed.88222160514
|View full text |Cite
|
Sign up to set email alerts
|

Farmacovigilância De Eventos Adversos No Pós-Vacinação Contra Covid-19 Durante a Gravidez E a Amamentação

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Open access publication by Atena Editora Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição-Não-Comercial-NãoDerivativos 4.0 Internacional (CC BY-NC-ND 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores, inclusive não representam necessariamente a posição oficial da Atena Editora. Permitido o download da obra e o compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Several other studies have also identified headache as the most prevalent AEFV in this context. In a Brazilian study conducted with workers from the Hospital de Clínicas de Porto Alegre, among 548 records, headache was present in 16% of cases, being the most reported systemic manifestation by the authors (13). Headache as an AEFV after Covid-19 vaccination primarily affected brown-skinned women aged 30 to 40, although these conditions also had the highest number of cases compared to all reported events.…”
Section: Discussionmentioning
confidence: 96%
“…Several other studies have also identified headache as the most prevalent AEFV in this context. In a Brazilian study conducted with workers from the Hospital de Clínicas de Porto Alegre, among 548 records, headache was present in 16% of cases, being the most reported systemic manifestation by the authors (13). Headache as an AEFV after Covid-19 vaccination primarily affected brown-skinned women aged 30 to 40, although these conditions also had the highest number of cases compared to all reported events.…”
Section: Discussionmentioning
confidence: 96%
“…Comparando-se o ano de 2021 com 2019, houve diminuição no número de pacientes atendidos, em quase todos os indicadores, com exceção dos AD. Em contrapartida, como previsto por Silva, Silva 26 (2020), no ano de 2021, foi possível a retomada da economia, a maior circulação de pessoas e da normalidade de atendimentos, resultando, conforme observado, em um aumento nos atendimentos realizados em quase todos os indicadores, a exceção foram os BZD.…”
Section: Discussionunclassified
“…As discussões sobre o isolamento social e sobre restrições à circulação das pessoas são pontos centrais para a determinação de políticas de contenção da doença. Segundo Silva e Silva (2) , a adoção de um isolamento horizontal, que abrange toda a população num posicionamento humanista, visa a proteger a vida acima de quaisquer outras preocupações.…”
Section: Introductionunclassified